Building climate-sensitive displacement statistics in Honduras - Taiwo, Ibukunoluwa (2025)
CGIAR is supporting Honduras’ National Institute of Statistics to integrate climate and displacement into national surveys. By strengthening household data systems, the collaboration makes climate-driven mobility and vulnerability visible, improving evidence for policies that anticipate displacement and support affected communities.